Community Pantry as a Form of Bayanihan in the Light of Albert Camus’ Concept of Rebellion - Hernandez, Carl Jayson D (Archīum Ateneo, 2024)
Filipinos are known for their traditional value called bayanihan. Bayanihan is a deeply embedded Filipino cultural idea symbolizing social solidarity and collaboration. During the COVID-19 pandemic, Filipinos created community pantries as a support system. This paper aims to analyze the idea of community pantry as a form of bayanihan through the Camusian perspective. The paper has three main parts. First, we will discuss the community pantry as a new form of bayanihan. This traditional value has been culturally passed to Filipinos and continues to live on as an identifier of the nation’s resiliency. Second, we will discuss Albert Camus’ concept of rebellion. Camus introduces the concept of the meridian, wherein one finds a sense of moderation in sharing the world’s struggle with their fellowmen. Third, we will attempt to reconcile Camus’ notion of rebellion and how the community pantries can be understood as a form of bayanihan. Hence, we propose that the meridian is present in the phenomenon of the community pantries as it manifests bayanihan as an act that shares Filipinos’ struggle during the COVID-19 pandemic.